2016
DOI: 10.1061/(asce)gt.1943-5606.0001461
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Shear Strains for Cyclic Degradation and Cyclic Pore Water Pressure Generation in Two Clays

Abstract: Cyclic threshold shear strains are fundamental cyclic soil properties that have not been fully investigated. To learn more about the threshold shear strains for cyclic degradation, γ td , and cyclic pore water pressure generation, γ tp , in fully saturated clays, nine multistage cyclic strain-controlled NGI direct simple shear tests are conducted on laboratory-made kaolinite clay (PI ¼ 28) and kaolinite-bentonite clay (PI ¼ 55). Three levels of vertical effective consolidation stress, σ 0 vc (113 kPa, approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Hyde and Ward, 1986;Yasuhara et al, 2003;Thian and Lee, 2017). Additionally, Vucetic (1994) and Mortezaie and Vucetic (2016) showed that below a certain shear strain value, termed the 'cyclic threshold shear strain', cyclic degradation does not occur to any significant degree. The magnitude of the cyclic threshold strain value is typically considered to be unaffected by the previous cyclic loading history.…”
Section: Cyclic Behaviourmentioning
confidence: 99%
“…Hyde and Ward, 1986;Yasuhara et al, 2003;Thian and Lee, 2017). Additionally, Vucetic (1994) and Mortezaie and Vucetic (2016) showed that below a certain shear strain value, termed the 'cyclic threshold shear strain', cyclic degradation does not occur to any significant degree. The magnitude of the cyclic threshold strain value is typically considered to be unaffected by the previous cyclic loading history.…”
Section: Cyclic Behaviourmentioning
confidence: 99%
“…In turn, a pronounced pore water pressure build-up can be identified from the first c levels. Looking at the main characteristics of the outliers (Table 2), it is evident that, first of all, tp values (ranging from 0.0005 to 0.007%) are totally out of the expected range of values (for example Mortezaie and Vucetic 2016 identified tp values which range from 0.014 to 0.034% for two reconstituted clays). These low tp values may be partially due to excessive sample disturbance effects that destroyed the soils structure, given the low V S,lab ∕V S,field observed, less than 0.6 for 4 outliers.…”
Section: Cyclic Threshold Shear Strainsmentioning
confidence: 99%
“…Above tv , at medium to large strains, soils exhibit a gradual degradation behaviour, experiencing permanent changes in the microstructure and, in drained conditions, volume variation. Vucetic (1994) and more recently Tabata and Vucetic (2010) and Mortezaie and Vucetic (2016) distinguished the amplitude below which there is practically no degradation, defined as cyclic degradation threshold shear strain ( td ), and the amplitude below which there is practically no permanent cyclic pore water pressure build-up, known as cyclic pore-water pressure generation threshold shear strain ( tp ). td is typically smaller than tv and the ratio tp ∕ td varies between 1.2 and 1.6.…”
Section: Introductionmentioning
confidence: 99%
“…When fully saturated soils are subjected to cyclic loading in undrained conditions involving moderate and large cyclic stress levels, their structure is permanently altered, the generation of excess porewater pressure and thus to a deterioration of bearing capacity and soil stiffness [1][2][3]. In undrained conditions, cyclic degradation of stiffness and cyclic pore water pressure changes are among the most important phenomena in soil dynamics [4]. The degradation of soils will then significantly influence the development of the accumulation of plastic strains and resilient stiffness.…”
Section: Introductionmentioning
confidence: 99%